2010
DOI: 10.1177/1557988309356100
|View full text |Cite
|
Sign up to set email alerts
|

Survey of State Public Health Department Resources for Men and Boys: Identification of an Inadvertent and Remediatable Service and Health Disparity

Abstract: State Public Health Departments (SPHDs) provide critical access to health outreach and services. Important strides have been made in these areas for broad ranges of populations; however, many men's health advocates believe that services to achieve similar goals for men and boys have inadvertently declined creating an unintended, but remediatable, service and health disparity. In 2008, the Men's Health Network completed a benchmarking survey of SPHDs to investigate the validity of concerns about this disparity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…Men have poorer overall health status and health outcomes (S. T. Williams & Giorgianni, 2010). This survey demonstrates a distinct lack of formal academic and training programs in men's health, including in health professional and public health programs.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Men have poorer overall health status and health outcomes (S. T. Williams & Giorgianni, 2010). This survey demonstrates a distinct lack of formal academic and training programs in men's health, including in health professional and public health programs.…”
Section: Discussionmentioning
confidence: 90%
“…Although health care practitioners, institutions, and policymakers have generally acknowledged the need for gender appropriate interventions, the U.S. health infrastructure has not developed gender-based strategies, resources, or approaches that address the comprehensive needs and preferences of men and boys (S. T. Williams & Giorgianni, 2010). This is in part because historically there has been little research focused on how to structure, implement, and evaluate different approaches to meeting the lifelong health needs of men and boys.…”
Section: Introductionmentioning
confidence: 99%
“…These explanations highlight individual risk, responsibility, and blame, which decontextualize risk behaviors and overlook the valid frames that highlight the ways in which health behaviors are culturally generated and structurally maintained. Framing men’s health in this manner blames men for their poor health outcomes versus blaming the lack of research, professional education in men’s health as a specialization ( Porche, 2007 ), or population health infrastructure to address men’s health ( Porche, 2010 ; Williams & Giorgianni, 2010 ). Defining and approaching men’s health in this manner, while congruent with cultural and political beliefs about the role of agency and personal responsibility in men’s health, neglects the cultural, social, and built environmental context that affords men the opportunity to engage in certain health practices more than others ( Griffith, 2016 ; Jackson & Knight, 2006 ).…”
Section: What Is Men’s Health and What Are Some Challenges With Currementioning
confidence: 99%
“…A research conducted in England noted that while men are seen as "difficult to access group", little attention has been given to health policies to assess the easiness and difficulties that interfere with preventative activities with men ( 2 . As well as a research conducted in the United States showed a shortage of resources for the health of men, significantly lower when compared to those dedicated to other population segments 3 .…”
Section: Introductionmentioning
confidence: 99%